2019
DOI: 10.1039/c8sm01850b
|View full text |Cite
|
Sign up to set email alerts
|

Surface relief of magnetoactive elastomeric films in a homogeneous magnetic field: molecular dynamics simulations

Abstract: The structure of a thin magnetoactive elastomeric (MAE) film adsorbed on a solid substrate is studied by molecular dynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Recently, some researchers [19][20][21][22] have found that the surface microstructures of MRE will change under the influence of the magnetic field, which provides a new idea for exploring the mechanism of magnetroncontrolled friction of MRE. In previous studies [23], we found that the surface roughness of MRE would change under the action of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers [19][20][21][22] have found that the surface microstructures of MRE will change under the influence of the magnetic field, which provides a new idea for exploring the mechanism of magnetroncontrolled friction of MRE. In previous studies [23], we found that the surface roughness of MRE would change under the action of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…A similar simple approach was introduced very recently to model the magnetoelastic response of thin film elastomeric coatings. 55 Each spring i corresponds to a simple harmonic potential:…”
Section: Model Interactionsmentioning
confidence: 99%
“…52 Numerous models use elastic springs to represent the mechanical constraints of the polymer matrix on the magnetic particles, either based on some fixed reference frame 33,35 or on an interconnected network of particles and springs. 45,47,48,50,[53][54][55] Explicit bead-spring monomer representations of the polymers, as the ones used in some models of magnetic gels, [56][57][58][59] still seem too expensive to provide useful insights on MEs. Another important simplification required by these models is the treatment of the magnetic properties of the embedded particles.…”
Section: Introductionmentioning
confidence: 99%
“…The change of MAE elastic modules has been defined as the magnetorheological effect (MRE) [14][15][16][17][18]. Due to all their abovementioned properties, MAE are now classified as smart materials [19,20].…”
Section: Introductionmentioning
confidence: 99%